Design of E-Public Service in Realizing Agile Government Based on Information Technology: Case Study in Indonesia - Dyah Mutiarin; Ririn Sudiro; Misran Misran (Indonesian Association for Public Administration (IAPA), 2021)
E-Public services based on information technology have been improved during the industrial revolution 4.0. Implementing E-Public Service leads to transforming public services in government from the old designs to the new designs that can assist in realizing agile government models. The agile government model is a model of government that creates a culture of agile and intelligent bureaucracy. This model focuses on the requirements of speed and ease in government processes, including public services. This study aims to explain the design of e-Public Service in realizing the Agile Government model. This study uses a qualitative descriptive approach assisted by NVivo 12 software in processing data. This study shows that the design of public Service in realizing an agile government model based on information technology is creating responsive public services, facilitating and accelerating the process of public services, and improving the quality of effective and efficient public services.